A CONCEPTUAL REVIEW ON LINGUISTIC APPROACHES OF IDENTITY INVESTIGATION - Susilowati, Meinarni (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2014)
Identity has been a blossoming issue in different fields. The intensity of investigating identity has stimulated the diverse methods and approaches to study identity from different angles. This paper discusses the how identity can be investigated from three different linguistic approaches, sociolinguistics, discourse analysis, and sociocultural linguistics approach. The practicality of these three approaches is explored to detect the nature of identity which is fluid, multiple, fragmented, socially, culturally, historically, religiously, and politically constructed and emerges within interactions. More space, however, is invested for elaborating the five principles of sociocultural linguistic approach due to its flexibility and multidimension of the approach. Empirical data is provided for proving its practicality for identity investigation. Further areas of investigation is given at the last part of the paper.